Managerial Response To Environmentally Induced Stress - Anderson, Carl R.; Hellriegel, Don; Slocum, John W. (Academy of Management Journal, 1977)
Results of a test of managerial response to environmentally induced stress indicated that locus of control was highly related to perception of stress in- the environment and the use of decision or coping behaviors. Performance was significantly related to the use of task-oriented coping behaviors. Implications for decision theory and the management of stress are discussed.